Preparation method of core-shell structure composite particles with dual response of color change / temperature and application thereof in mesenchymal stem cell suspension culture
Patent Information
- Application Number
- CN202311671509.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-07
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2043-12-07
AI Technical Summary
但在大规模细胞生产中还存在一定的问题:(1)对微载体的要求较高
1)将间充质干细胞贴壁培养在一定数量直径相同质量不同的变色/温度双重响应核壳结构复合颗粒上,利用培养容器上方施加的静磁场对复合颗粒中铁珠的磁吸作用与复合颗粒因质量不同产生的不同重力之间的平衡,使贴附有细胞的复合颗粒均匀的分层悬浮在培养体系中并保持相对静止,避免复合颗粒因堆叠或不断悬浮于培养体系中而造成贴附有细胞的复合颗粒间不断碰撞摩擦导致复合颗粒缺损和对细胞造成不可逆的机械损伤。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of cell culture technology, specifically to a method for preparing a core-shell composite particle with dual color change / temperature response and its application in the suspension culture of mesenchymal stem cells, thereby enabling the large-scale production of adherent mesenchymal stem cells. Background Technology
[0002] Animal cells cultured in vitro mainly grow in two ways: adherent growth and suspension growth. As the name suggests, adherent growth requires cells to attach to a substrate to proliferate, while suspension growth refers to a culture method where cells can freely suspend in the culture medium to grow and proliferate. Suspension-grown cells are very simple to culture and passage. During culture, cells are simply seeded at a certain density in a suitable culture medium and placed under specific culture conditions for good growth. Passaging does not require further dispersion; cells can simply be diluted proportionally and cultured again. Cells cultured using this method proliferate rapidly, yield highly, and the culture process is simple, making it one of the ideal models for large-scale animal cell culture. In contrast, traditional adherent cell culture methods include roller bottle culture, multilayer plate culture, and stirred microcarrier culture. Roller flasks and multi-layer plate cultures are commonly used in the early and middle stages of product development. However, both methods are not only cumbersome to operate, but also exhibit both contact inhibition and density inhibition due to the limited adhesion area and poor mass and oxygen transfer. Cells coming into contact with each other inhibit cell movement, preventing them from overlapping and growing. Even after cell growth and aggregation, contact inhibition persists, but proliferation and division continue as long as nutrients are sufficient. However, once a certain cell density is reached, cell division ceases due to nutrient depletion and the influence of metabolites—a phenomenon known as density inhibition. This significantly limits the practical application of adherent cells in production and makes them unsuitable for large-scale manufacturing.
[0003] With the advancement of technology in recent years, stirred microcarrier culture, a modified method of adherent cell culture, has been applied to large-scale animal cell culture. The microcarrier culture method involves mixing a prepared cell suspension with microcarriers that have been pre-soaked and sterilized in serum (to accelerate cell adhesion). After incubation for a period of time, once the cells have adhered to the microcarriers, they are transferred to a culture medium and a gentle stirring system is used to ensure uniform suspension of the cells along with the carriers. The microcarriers used are typically solid beads of a certain diameter, and the materials generally fall into five categories: cellulose, plastics, gelatin, glass, and dextran. In recent years, various other microcarrier materials have been developed abroad, such as liquid microcarriers, polystyrene microcarriers, PHEMA microcarriers, chitin microcarriers, and alginate gel microcarriers. Microcarrier culture has overcome the shortcomings of the initial roller bottle culture to a certain extent and has many advantages: (1) It combines the advantages of monolayer culture and suspension culture, and is a homogeneous culture; (2) The cell environment is uniform; (3) Environmental conditions (temperature, pH and CO2, etc.) are easy to measure and monitor; (4) It has a high specific surface area; (5) The culture operation can be systematized and automated, reducing the chance of contamination. Although microcarrier culture technology has made great progress in many technical aspects after decades of development, there are still some problems in large-scale cell production: (1) The requirements for microcarriers are high. As cells adhere and grow, the concentration of microcarriers should be gradually increased to provide more and more surface area required for cell growth. However, under the condition that the culture system and culture method are determined, the concentration of microcarriers cannot be increased indefinitely, and cell growth and metabolism will be inhibited when the concentration of microcarriers reaches a critical value. (2) The efficiency of cell expansion is affected and limited by many factors, including the sensitivity of seed cells to shear force, the nutrient supply after cells reach high density, the accumulation of metabolites, and passage and expansion culture. In particular, apoptosis causes large-scale cell death, which can seriously affect the maintenance of high cell activity and high density. (3) Microcarriers for culture are quite expensive. (4) Some carriers are non-degradable, thus limiting their clinical application. Summary of the Invention
[0004] The purpose of this invention is to provide a method for preparing core-shell composite particles with dual color-changing / temperature response and their application in mesenchymal stem cell suspension culture.
[0005] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A color-changing / temperature-responsive core-shell composite particle, wherein the core-shell composite particle is spherical with a diameter of 2.5 mm and consists of a core and an outer shell; the core is a high-purity iron bead with a diameter of 1 mm, and the outer shell includes a first shell, a second shell, and a third shell; the first shell is color-changing silicone coated on the surface of the core; the second shell is a PU waterproof membrane coated on the surface of the first shell; and the third shell is N-isopropylacrylamide thermosensitive hydrogel coated on the surface of the second shell.
[0006] The preparation method of the above-mentioned core-shell structured composite particles includes the following steps: S1: Kernel preparation: Purchase high-purity iron beads, each with a diameter of 1mm and a weight of 1.0mg, 1.5mg, 2.0mg, 2.5mg, 3.0mg, 3.5mg, 4.0mg, 4.5mg, and 5.0mg, for later use; S2: Cover the core surface with a first shell: S2-1: Absorbed density 1.25 g / cm³ 3 A 6% Na2O dilute sodium silicate solution was allowed to stand and clarify, and then mixed with an equal volume of a 20% (w / w) dilute sulfuric acid solution. The mixture was stirred until homogeneous to obtain a sodium silicate-sulfuric acid mixed solution. S2-2: Immerse the high-purity iron beads prepared in step S1 into the sodium silicate-sulfuric acid mixed solution obtained in step S2-1 for 5 seconds, quickly lift them out with a sieve, and shake the sieve to drain excess sodium silicate-sulfuric acid mixed solution until no liquid drips from the surface of the iron beads, thus obtaining iron beads with the sodium silicate-sulfuric acid mixed solution on their surface; then, bathe the iron beads with the sodium silicate-sulfuric acid mixed solution on their surface in an 80°C hot oil bath for 5 seconds to obtain iron-containing silica gel particles; after the hot oil bath, cool the iron-containing silica gel particles with circulating water to remove surface oil, and then separate the iron-containing silica gel particles with a diameter of 1.25 mm through a sieve for later use; S2-3: Immerse the 1.25 mm diameter iron-containing silica gel particles obtained in step S2-2 into a 2% (w / w) dilute sulfuric acid solution, react at 25°C for 16 h, and then wash with distilled water until neutral. S2-4: Dissolve 170g cobalt chloride and 60g ammonium chloride in 1000mL distilled water, add 5mL of 16% ammonia water to obtain a dilute cobalt chloride dye solution; then immerse the iron-containing silica gel particles obtained in step S2-3 in the dilute cobalt chloride dye solution for 6h, dry at 110℃ for 20h, and sterilize with gamma rays to obtain sterile discolored iron-containing silica gel particles; S3: Cover the surface of the first shell with a second shell: S3-1: Add 10.32g of polyurethane to 100mL of N,N-dimethylformamide and stir magnetically until completely dissolved under sealed conditions at room temperature to obtain PU electrospinning solution; S3-2: Inject the PU electrospinning solution obtained in step S3-1 into the syringe of the electrospinning equipment, add a stainless steel needle to the front end of the syringe, and electrospin the surface of the sterile discoloration iron-containing silica particles obtained in step S2-4 to obtain sterile discoloration iron-containing silica particles with PU electrospinning solution uniformly adhered to the surface. Dry them in vacuum at 50°C for 6 hours to remove residual solvent for later use. S3-3: Immerse the sterile, color-changing, iron-containing silica gel particles with PU electrospinning solution uniformly adhered to the surface after removing residual solvent in step S3-2 in sterile water, remove unqualified defective products, and the resulting PU waterproof sterile, color-changing, iron-containing silica gel particles are sterile and ready for use. S4: Preparation of porous transparent N-isopropylacrylamide hydrogel: S4-1: Dissolve active dry yeast and glucose in sterile water at 37℃ and let stand for 30 min to activate the yeast to obtain yeast activation solution; S4-2: Dissolve N-isopropylacrylamide monomer, N,N'-methylenebisacrylamide and wheat gliadin in a beaker containing the yeast activation solution from step S4-1. After sealing the beaker, replace the air in the beaker with N2 and stir for 20 min under the N2 atmosphere. Then add 0.1 g of ammonium persulfate and continue stirring for 10 min. Then add 0.4 mL of tetramethylethylenediamine and continue stirring until gel-like to obtain a porous transparent N-isopropylacrylamide thermosensitive hydrogel. S5: Cover the surface of the second shell with a third shell: S5-1: Slowly immerse the PU waterproof sterile color-changing iron-containing silica gel particles obtained in step S3-3 into the porous transparent N-isopropylacrylamide thermosensitive hydrogel obtained in step S4-2, stir evenly, sonicate in an oil bath at 25°C for 30 minutes, let stand for 1 hour, and then let stand at 40°C for 30 minutes to obtain PU waterproof sterile color-changing iron-containing silica gel particles with porous transparent N-isopropylacrylamide thermosensitive hydrogel on the surface. After removing the surface oil, sort out the particles with a diameter of 2.5 mm to obtain core-shell structure composite particles with color-changing / temperature dual response containing iron beads of different masses. S5-2: Soak the color-changing / temperature-responsive composite particles obtained in step S5-1 in anhydrous ethanol at room temperature for 3 days, replacing the anhydrous ethanol every 12 hours. Then soak them in sterile deionized water at room temperature for 3 days, replacing the deionized water every 12 hours. Finally, store them in sterile deionized water for later use. In step S4, the mass ratio of the active dry yeast to N-isopropylacrylamide monomer is 1:4. In step S4, the glucose content in the yeast activation solution is 5% to 10% by mass. In step S4, the mass fraction of wheat gliadin in the porous transparent N-isopropylacrylamide thermosensitive hydrogel is 12% to 15%.
[0007] The application of the color-changing / temperature-responsive core-shell composite particles prepared by the above method in the suspension culture of mesenchymal stem cells.
[0008] A method for culturing mesenchymal stem cells using color-changing / temperature-responsive core-shell composite particles prepared by the above method involves adhering mesenchymal stem cells to core-shell composite particles of different masses. A static magnetic field is used to uniformly suspend the cell-adhered composite particles in the culture system, maintaining them relatively still. When the mesenchymal stem cells grow to a certain density, the temperature is lowered to below 32°C. The volume phase transition properties of a porous, transparent N-isopropylacrylamide thermosensitive hydrogel are used to automatically detach the adhering cells from the core-shell composite particles. After the adhering cells detach, the direction of the static magnetic field is changed to cause the core-shell composite particles to aggregate and fix at the bottom of the culture container. The cell suspension above the core-shell composite particles is then aspirated and centrifuged to obtain the mesenchymal stem cell precipitate. The method specifically includes the following steps: S1: Different masses of color-changing / temperature-responsive core-shell composite particles are laid at the bottom of the culture container. Then, the mesenchymal stem cells to be inoculated are added to an appropriate amount of complete culture medium, mixed well, and inoculated into the culture container. The culture container is then placed vertically in an incubator at 37°C and 5% CO2. A static magnetic field is applied above the culture container to make the core-shell composite particles with attached cells uniformly layered and suspended in the culture system and kept relatively still. S2: After the mesenchymal stem cells in step S1 have reached 80% cell confluence, adjust the incubator temperature to 20℃ and continue culturing until all the nuclear-shell composite particles change color from colorless to blue, indicating that the mesenchymal stem cells have completely detached from the nuclear-shell composite particles. S3: After the mesenchymal stem cells in step S2 have completely detached from the core-shell composite particles, turn off the static magnetic field above the culture container. After all the core-shell composite particles have naturally settled to the bottom of the culture container, apply a static magnetic field to the bottom of the culture container to make the core-shell composite particles gather and fix to the bottom of the culture container. Take the cell suspension above the core-shell composite particles and centrifuge it. Discard the supernatant to obtain the mesenchymal stem cell precipitate. The strength of the static magnetic field is 5 mT to 1 T.
[0009] The significant advantages of this invention are: 1) Mesenchymal stem cells are cultured adherently on a certain number of color-changing / temperature-responsive core-shell composite particles of the same diameter but different masses. The static magnetic field applied above the culture vessel balances the magnetic attraction of the iron beads in the composite particles with the different gravitational forces generated by the different masses of the composite particles. This allows the composite particles with attached cells to be uniformly layered and suspended in the culture system and remain relatively still. This avoids the composite particles from being stacked or continuously suspended in the culture system, which would cause continuous collisions and friction between the composite particles with attached cells, resulting in composite particle defects and irreversible mechanical damage to the cells.
[0010] 2) The first shell of the color-changing / temperature-responsive core-shell composite particles is color-changing silica gel, the second shell is a PU waterproof membrane, and the third shell is N-isopropylacrylamide thermosensitive hydrogel. The color-changing silica gel is blue in anhydrous conditions and turns pink upon absorbing water. Both the PU waterproof membrane and the N-isopropylacrylamide hydrogel are transparent; therefore, the presence of the color-changing silica gel makes the entire core-shell composite particle appear blue. The PU waterproof membrane provides waterproofing. The combination of the color-changing silica gel and the PU waterproof membrane plays a crucial role in the recycling of the color-changing / temperature-responsive core-shell composite particles. If the third shell, the N-isopropylacrylamide thermosensitive hydrogel, is severely damaged, it will remove the waterproof membrane adhering to the damaged hydrogel, causing the color-changing silica gel to absorb water and turn pink, thus discarding the composite particle. When the core-shell composite particles are suspended in the culture system, the blue color indicates whether the particles are uniformly layered and suspended in the system. Mesenchymal stem cells grow attached to a color-changing / temperature-responsive core-shell composite particle. The degree of cell confluence can be roughly judged by the degree of disappearance of the blue color in the culture system. At the same time, the degree of automatic detachment of adherent cells after the temperature is reduced can also be determined by the overall color change of the composite particle from colorless to blue.
[0011] 3) Poly(N-isopropylacrylamide) is a thermoresponsive polymer that undergoes a volume phase transition at 32°C, i.e., its LCST (lowest critical solution temperature) is 32°C. When the ambient temperature is below the LCST, hydrogen bonds between water molecules and amide bonds promote the formation of a stable hydrated structure around the isopropyl group in the molecular chain. When the ambient temperature rises, the hydrated structure decomposes, and non-hydrated hydrogen bonds between amide groups and hydrophobic interactions originating from the isopropyl group play a major role, forcing the water molecules initially bound to N-isopropylacrylamide to diffuse outward. Leveraging this property, N-isopropylacrylamide thermosensitive hydrogels with both hydrophilic and hydrophobic groups and a thermal response time shortened to 30-45 minutes were prepared. When used as a carrier in in vitro cell culture, these hydrogels enhance the adhesion, proliferation, and cytokine secretion of adherent cells. Upon cooling below the LCST, adherent cells, along with integrated membrane proteins and most intercellular junction proteins, spontaneously detach from the thermosensitive surface, preventing damage to cell membrane proteins and cell function caused by trypsin digestion. This helps protect the ultrastructure and function of the target cells. In contrast, hydrogels prepared using traditional methods have slow response times, with cell detachment sometimes requiring up to a day.
[0012] 4) The alcohol-soluble proteins in the porous, transparent N-isopropylacrylamide thermosensitive hydrogel can form a mesh during preparation to trap the carbon dioxide gas produced by the anaerobic respiration of yeast, preventing gas leakage. The hydrogel gradually forms a sponge-like porous structure. This porous structure accelerates gel volume changes, increases the rate of thermal response, and speeds up cell detachment. The numerous but small pores accelerate the response while preventing excessively large pores from causing cell migration into the hydrogel during growth.
[0013] 5) In addition to suspending the composite particles, a static magnetic field within a certain range can also cause significant changes in cell morphology, DNA, RNA, protein synthesis, transmembrane transport, and enzyme activity in the culture system, reducing the proportion of resting cells in the cell growth cycle. At the same time, due to the antimagnetic anisotropy of the plasma membrane, the structure of the plasma membrane changes under the action of the magnetic field, which improves the ion transport capacity of the cell membrane and ultimately promotes the proliferation rate of mesenchymal stem cells.
[0014] 6) Within a certain range, the number of cells harvested is related to the size of the culture container, the number of composite particles used in the culture, the diameter of the composite particles, the degree of change in the weight gradient of the composite particles, the magnitude of the static magnetic field, and the distance of the static magnetic field. The larger the culture container, the more suspended composite particles it can hold. The more composite particles there are, the greater the area for cell adhesion and growth, and thus, large-scale production of adherent cells can be achieved. Attached Figure Description
[0015] Figure 1This image shows a color comparison between intact and damaged color-changing / temperature-responsive composite particles after absorbing water. A represents an intact color-changing / temperature-responsive composite particle, which turns blue after absorbing water; B represents a damaged color-changing / temperature-responsive composite particle, which turns pink after absorbing water. The arrow in B indicates the broken, transparent third-layer N-isopropylacrylamide thermosensitive hydrogel.
[0016] Figure 2 This is a scanning electron microscope image of N-isopropylacrylamide thermosensitive hydrogel.
[0017] Figure 3 It is the water retention rate of color-changing / temperature-responsive composite particles.
[0018] Figure 4 This is a diagram showing the state of mesenchymal cell culture. Detailed Implementation
[0019] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.
[0020] Example 1 A method for culturing mesenchymal stem cells in suspension, comprising the following steps: S1: Kernel preparation: High-purity iron beads of different weights (1.0mg, 1.5mg, 2.0mg, 2.5mg, 3.0mg, 3.5mg, 4.0mg, 4.5mg, and 5.0mg) were purchased for use. The high-purity iron beads had a dense and smooth surface, a particle size of 1mm, and a purity greater than 99.99%.
[0021] S2: Cover the core surface with a first shell: S2-1: Take a sample of dilute sodium silicate solution (density 1.25 g / cm³). 3 (Na2O content 6%) was left to stand for 30 minutes to clarify, and then mixed with an equal volume of 20% dilute sulfuric acid solution and stirred evenly to obtain sodium silicate-sulfuric acid mixed solution.
[0022] S2-2: Immerse the iron beads of different masses prepared in step S1 into the sodium silicate-sulfuric acid mixed solution obtained in step S2-1 for 5 seconds to ensure that the sodium silicate-sulfuric acid mixed solution evenly coats the surface of the iron beads. After immersion, quickly remove the iron beads with a sieve and vibrate the sieve to drain excess sodium silicate-sulfuric acid mixed solution until no more liquid drips from the surface of the iron beads, thus obtaining iron beads with the sodium silicate-sulfuric acid mixed solution coated on the surface. Place the iron beads coated with the sodium silicate-sulfuric acid mixed solution in a hot oil bath with hot air at 80°C for 5 seconds for heat treatment. To allow the sodium silicate-sulfuric acid mixed solution coating the iron beads to solidify into silica gel upon heating, iron-containing silica gel particles were obtained. After heat treatment, the iron-containing silica gel particles were cooled with room temperature circulating water for 3 minutes, and then the surface oil was removed with a compound oxalic acid cleaning agent with a pH of 4 (purchased from Dongguan Precision Chemical Technology Co., Ltd., product number JD-801), resulting in iron-containing silica gel particles with the surface oil removed. The iron-containing silica gel particles with the surface oil removed were sieved, and the iron-containing silica gel particles with a particle size of 1.25 mm were selected for later use.
[0023] S2-3: Immerse the iron-containing silica gel particles with a particle size of 1.25 mm that have been degreased in step S2-2 into a 2% (w / w) dilute sulfuric acid solution and react at 25°C for 16 h. Then wash with distilled water until neutral.
[0024] S2-4: Dissolve 170g cobalt chloride and 60g ammonium chloride in 1000mL of distilled water, add 5mL of 16% ammonia water to obtain a dilute cobalt chloride dye solution; then immerse the iron-containing silica gel particles obtained in step S2-3 in the dilute cobalt chloride dye solution for 6h, dry at 110℃ for 20h, and sterilize with gamma rays to obtain sterile discolored iron-containing silica gel particles.
[0025] S3: Cover the surface of the first shell with a second shell: S3-1: Add 10.32g of polyurethane (PU) powder to 100mL of N,N-dimethylformamide (DMF) solvent, and stir magnetically for about 12h under sealed conditions at room temperature until completely dissolved to obtain a PU electrospinning solution with a mass fraction of 18%.
[0026] S3-2: Inject the PU electrospinning solution obtained in step S3-1 into the syringe of the electrospinning equipment. Add a stainless steel needle with a diameter of 0.4 mm to the front end of the syringe. Electrospin the sterile discoloration iron-containing silica particles for 6 hours under the conditions of voltage of 15 kV, spinning rate of 0.6 ml / h, receiving distance of 17 cm, temperature of 40℃ and relative humidity of 35%, to obtain sterile discoloration iron-containing silica particles with PU electrospinning solution uniformly adhered to the surface. Dry them under vacuum at 50℃ for 6 hours to remove residual solvent for later use.
[0027] S3-3: Immerse the sterile, color-changing, iron-containing silica gel particles with PU electrospinning solution uniformly adhered to their surface after removing residual solvent in step S3-2 in sterile water for 0.5 hours. Remove any defective products to obtain PU waterproof sterile, color-changing, iron-containing silica gel particles. Dry these particles in a sterile drying oven at 110°C for 2 hours for later use. The defective products exhibit the characteristic of changing from blue to pink upon immersion in sterile water, indicating that their surface waterproof film is incomplete.
[0028] S4: Preparation of porous transparent N-isopropylacrylamide hydrogel S4-1: Dissolve 1g of active dry yeast and 2.5g of glucose in 50mL of sterile water at 37℃, and let stand for 30min to activate the yeast to obtain an activated yeast solution. The active dry yeast is Angel low-sugar high-activity dry yeast (produced by Angel Yeast Co., Ltd.).
[0029] S4-2: Dissolve 4g N-isopropylacrylamide, 0.25g N,N'-methylenebisacrylamide and 6g wheat gliadin in a beaker containing 50mL of yeast activation solution from step S4-1. After sealing the beaker, use N2 to purge the air from the beaker. Stir at 500r / min for 20min under N2 atmosphere. Then add 0.1g ammonium persulfate (APS) and continue stirring under N2 atmosphere for 10min. Finally, add 0.4mL tetramethylethylenediamine (TEMED) and continue stirring under N2 atmosphere for 10min until gelation occurs, resulting in a porous transparent N-isopropylacrylamide hydrogel.
[0030] S5: Coating the surface of the second shell with a third shell (preparing color-changing / temperature-responsive composite particles): S5-1: Slowly immerse the PU waterproof sterile color-changing iron-containing silica gel particles obtained in step S3-3 into the porous transparent N-isopropylacrylamide hydrogel obtained in step S4-2. After ultrasonic treatment in an oil bath at 25°C for 30 minutes, let it stand for 1 hour. Then raise the oil bath temperature to 40°C and let it stand for 30 minutes to allow the hydrogel to shrink uniformly, thus obtaining PU waterproof sterile color-changing iron-containing silica gel particles with porous transparent N-isopropylacrylamide hydrogel on the surface. After removing the surface oil stains from the PU waterproof sterile color-changing iron-containing silica gel particles with porous transparent N-isopropylacrylamide hydrogel, use a composite oxalic acid cleaning agent with a pH of 4 (purchased from Dongguan Precision Chemical Technology Co., Ltd., product number JD-801) and 70°C hot water, sort out the particles with a particle size of 2.5 mm to obtain color-changing / temperature-responsive composite particles with a particle size of 2.5 mm.
[0031] S5-2: Soak the color-changing / temperature-responsive composite particles obtained in step S5-1 in anhydrous ethanol at room temperature for 3 days, replacing the anhydrous ethanol every 12 hours, in order to clean the inactivated yeast, protein and yeast metabolites in the pores of the composite particles; then soak the composite particles in sterile deionized water at room temperature for 3 days, replacing the deionized water every 12 hours, and finally store them in sterile deionized water for later use.
[0032] S6: Umbilical cord mesenchymal stem cell culture and harvesting: S6-1: Take 600 of each of the 2.5mm color-changing / temperature-responsive composite particles containing 1.0mg, 1.5mg, 2.0mg, 2.5mg, 3.0mg, 3.5mg, 4.0mg, 4.5mg, and 5.0mg iron beads obtained in step S5-2, mix them evenly, and then spread them on the bottom of a Corning T175 culture flask (item number 431080).
[0033] S6-2: Preheat the constant temperature water bath to 42℃; remove a P4 generation umbilical cord mesenchymal stem cell cryopreservation tube from the liquid nitrogen tank, immediately immerse it in warm water and gently agitate until the cryopreservation solution is almost completely thawed. After disinfecting the cryopreservation tube with alcohol, transfer the cell suspension in the tube to a 50ml centrifuge tube pre-filled with 30ml of basal culture medium (Youkang mesenchymal stem cell serum-free culture medium, catalog number NC0103), take 100μl of sample, stain with trypan blue, and count the total number of cells to 1×10⁻⁶. 7 Cells were collected, with a viability of 98.26%. The remaining suspension was centrifuged at 500g for 6 min to collect the cell pellet, which was then resuspended in complete culture medium (500mL of Youkang mesenchymal stem cell serum-free culture medium with 5mL of Youkang additive, product number NC0103.S) until the cell density was 1×10⁻⁶ cells / mL. 6 Units / mL are available for use.
[0034] S6-3: Take 2.9 mL of the cell density from step S6-2, which is 1×10⁻⁶ cells / mL. 6 The umbilical cord mesenchymal stem cell suspension was added to a 50ml centrifuge tube pre-filled with 30ml of complete culture medium. The suspension was then seeded into a T175 culture flask without any treatment (control group) and a T175 culture flask with color change / temperature dual-response composite particles in step S6-1 (experimental group) and mixed well.
[0035] It should be noted that here, the number of mesenchymal stem cells seeded = seeding density × bottom area of the culture container × number of groups of iron beads of different masses, where the seeding density is 7 × 10⁻⁶. 3 ~9×10 3 pcs / cm 2 In this application, the T175 culture flask has dimensions of 11.5cm × 3.5cm × 15cm, and a base area of 11.5cm × 3.5cm = 40.25cm². 2The number of groups with iron beads of different qualities was 9; therefore, the seeding quantity of mesenchymal stem cells was 2.54 × 10⁻⁶. 6 ~3.26×10 6 indivual.
[0036] S6-4: Place the culture flasks of the control group and the experimental group horizontally in an incubator at 37℃ and 5% CO2. After 3 hours, add 120ml of complete culture medium to the T175 culture flask of the experimental group and mix gently. Then, place the culture flask of the experimental group vertically in an incubator at 37℃ and 5% CO2 and set a static magnetic field of 5mT at a distance of 25cm above the bottom of the culture flask so that the composite particles with attached cells are evenly layered and suspended in the culture system and remain relatively still.
[0037] S6-5: Harvest the cells when the confluence of the control group and the experimental group reaches 80% respectively: Control group cultured for 60h: Discard the old culture medium in the T175 bottle, add 10ml of physiological saline to wash twice, then digest with 10ml of 0.05% trypsin for 3min. Under the microscope, the adherent cells are observed to be round and 80% of the cells begin to detach from the wall. Immediately add 10ml of complete culture medium to stop digestion, blow the bottom of the bottle to transfer the cell suspension to a 50ml centrifuge tube, centrifuge at 500g for 6min, remove the supernatant and collect the precipitate; Experimental group cultured for 48h: Set the incubator temperature to 20℃. After 30min, the composite particles in the culture bottle can be observed to turn from colorless to blue, indicating that the cells have completely detached. Turn off the magnetic field and wait for the composite particles to sink to the bottom naturally. Then transfer the magnetic field to the bottom of the culture bottle to gather and fix the composite particles. Aspirate the cell suspension above the composite particles and transfer it to a 50ml centrifuge tube. Centrifuge at 500g for 6min, remove the supernatant and collect the precipitate.
[0038] S6-6: Resuspend the cell pellets from the experimental group and the control group in 45 ml of physiological saline, respectively. Take a certain volume of cell suspension from each group for cell counting and viability detection, and 2×10⁻⁶. 6 One cell was used for flow cytometry detection.
[0039] Figure 1 This image shows a color comparison between intact and damaged color-changing / temperature-responsive composite particles after absorbing water. A represents an intact color-changing / temperature-responsive composite particle, which remains blue after absorbing water; B represents a damaged color-changing / temperature-responsive composite particle, which changes from blue to pink after absorbing water. The arrow in B indicates the broken, transparent third shell N-isopropylacrylamide thermosensitive hydrogel, which is now transparent.
[0040] The color-changing / temperature-responsive composite particles were soaked in 20℃ warm water for 30 min to reach water absorption equilibrium. After removing and drying the surface moisture, they were pre-frozen in liquid nitrogen for 30 min, then freeze-dried for 1 h. After sectioning, the surface of the sections was sputter-coated with gold, and the internal pore size of the hydrogel was observed using a scanning electron microscope (SEM) at an accelerating voltage of 20 kV. The SEM image of the porous transparent N-isopropylacrylamide hydrogel is shown below. Figure 2 The hydrogel has a porous structure, and most of the pores in the porous structure have a pore size of less than 10 μm.
[0041] The color-changing / temperature-responsive composite particles were soaked in 20℃ warm water for 30 minutes to reach water absorption equilibrium. Then, they were removed and placed in 37℃ constant temperature water. Every 5 minutes, the surface moisture was wiped off and the particles were weighed until the sample mass remained constant, and the water retention rate was calculated. Figure 3 It can be seen that the porous transparent N-isopropylacrylamide hydrogel wrapped on the surface of the color change / temperature dual-response composite particles rapidly shrinks and loses most of the water in the pore structure in the first 10 minutes at 37℃, and the water loss is close to a stable state after 30 minutes.
[0042] Figure 4 The diagrams show the states of mesenchymal cell culture. A shows the color-changing / temperature-responsive composite particles with umbilical cord mesenchymal stem cells attached, suspended in layers and kept relatively static during culture; B shows the composite particles completely attached to the umbilical cord mesenchymal stem cells, with the color of the composite particles changing from blue to colorless; C shows the adherent cells detaching from the color-changing / temperature-responsive composite particles, forming the composite particles at the bottom of the flask where they settle and aggregate, with the cell suspension above.
[0043] The specific results of the umbilical cord mesenchymal stem cell test are as follows: 1) The cell counts and viability of the experimental group after 48 hours of culture and the control group after 60 hours of culture are shown in the table below: As shown in the table, compared to the control group, the experimental group had significantly higher cell migration and proliferation rates at a growth time when cell fusion reached 80%. The experimental group also harvested 7.1 times more cells than the control group with a shorter growth cycle, and the viability of the harvested cells was also superior.
[0044] 2) The flow cytometry results of the experimental group (cultured for 48 hours) and the control group (cultured for 60 hours) are shown in the table below: The flow cytometry analysis results in the table show that the surface marker CD90 of umbilical cord mesenchymal stem cells cultured in both the experimental and control groups... + CD73 + and CD105 +The positive expression rate was all above 95%, and CD45 + / CD34 + / CD11b + / CD19 + / HLA-DR + The positive rate was less than 2%, consistent with the phenotypic characteristics of mesenchymal stem cells. Furthermore, the data from the experimental group and the control group showed no significant difference, demonstrating that the culture method of this invention does not reduce the expression or alteration of the mesenchymal stem cell phenotype.
Claims
1. A core-shell structured composite particle with dual color-changing / temperature response, characterized in that: The core-shell composite particle is spherical with a diameter of 2.5 mm and consists of a core and an outer shell. The core is a high-purity iron bead with a diameter of 1 mm. The outer shell includes a first shell, a second shell, and a third shell. The first shell is color-changing silicone and covers the surface of the core. The second shell is a PU waterproof membrane and covers the surface of the first shell. The third shell is N-isopropylacrylamide thermosensitive hydrogel and covers the surface of the second shell.
2. The method for preparing core-shell structured composite particles as described in claim 1, characterized in that: Includes the following steps: S1: Kernel preparation: Purchase high-purity iron beads, each with a diameter of 1mm and a weight of 1.0mg, 1.5mg, 2.0mg, 2.5mg, 3.0mg, 3.5mg, 4.0mg, 4.5mg, and 5.0mg, for later use; S2: Cover the core surface with a first shell: S2-1: Absorbed density 1.25 g / cm³ 3 A 6% Na2O dilute sodium silicate solution was allowed to stand and clarify, and then mixed with an equal volume of a 20% (w / w) dilute sulfuric acid solution. The mixture was stirred until homogeneous to obtain a sodium silicate-sulfuric acid mixed solution. S2-2: Immerse the high-purity iron beads prepared in step S1 into the sodium silicate-sulfuric acid mixed solution obtained in step S2-1 for 5 seconds, quickly lift them out with a sieve, and shake the sieve to drain excess sodium silicate-sulfuric acid mixed solution until no liquid drips from the surface of the iron beads, thus obtaining iron beads with the sodium silicate-sulfuric acid mixed solution on their surface; then, bathe the iron beads with the sodium silicate-sulfuric acid mixed solution on their surface in an 80°C hot oil bath for 5 seconds to obtain iron-containing silica gel particles; after the hot oil bath, cool the iron-containing silica gel particles with circulating water to remove surface oil, and then separate the iron-containing silica gel particles with a diameter of 1.25 mm through a sieve for later use; S2-3: Immerse the 1.25 mm diameter iron-containing silica gel particles obtained in step S2-2 into a 2% (w / w) dilute sulfuric acid solution, react at 25°C for 16 h, and then wash with distilled water until neutral. S2-4: Dissolve 170g cobalt chloride and 60g ammonium chloride in 1000mL of distilled water, add 5mL of 16% ammonia water to obtain a dilute cobalt chloride dye solution; then immerse the iron-containing silica gel particles obtained in step S2-3 in the dilute cobalt chloride dye solution for 6h, dry at 110℃ for 20h, and sterilize with gamma rays to obtain sterile discolored iron-containing silica gel particles; S3: Cover the surface of the first shell with a second shell: S3-1: Add 10.32g of polyurethane to 100mL of N,N-dimethylformamide and stir magnetically until completely dissolved under sealed conditions at room temperature to obtain PU electrospinning solution; S3-2: Inject the PU electrospinning solution obtained in step S3-1 into the syringe of the electrospinning equipment, add a stainless steel needle to the front end of the syringe, and electrospin the surface of the sterile discoloration iron-containing silica particles obtained in step S2-4 to obtain sterile discoloration iron-containing silica particles with PU electrospinning solution uniformly adhered to the surface. Dry them in vacuum at 50°C for 6 hours to remove residual solvent for later use. S3-3: Immerse the sterile, color-changing, iron-containing silica gel particles with PU electrospinning solution uniformly adhered to the surface after removing residual solvent in step S3-2 in sterile water, remove unqualified defective products, and the resulting PU waterproof sterile, color-changing, iron-containing silica gel particles are sterile and ready for use. S4: Preparation of porous transparent N-isopropylacrylamide hydrogel: S4-1: Dissolve active dry yeast and glucose in sterile water at 37°C, let stand for 30 minutes to activate, and obtain yeast activation solution; S4-2: Dissolve N-isopropylacrylamide monomer, N,N'-methylenebisacrylamide and wheat gliadin in a beaker containing the yeast activation solution from step S4-1. After sealing the beaker, use N2 to purge the air from the beaker and stir for 20 min under the N2 atmosphere. Then add 0.1 g of ammonium persulfate and continue stirring for 10 min. Finally, add 0.4 mL of tetramethylethylenediamine and continue stirring until a gel is formed, resulting in a porous, transparent N-isopropylacrylamide thermosensitive hydrogel. S5: Cover the surface of the second shell with a third shell: S5-1: Slowly immerse the PU waterproof sterile color-changing iron-containing silica gel particles obtained in step S3-3 into the porous transparent N-isopropylacrylamide thermosensitive hydrogel obtained in step S4-2, stir evenly, sonicate in an oil bath at 25°C for 30 minutes, let stand for 1 hour, and then let stand at 40°C for 30 minutes to obtain PU waterproof sterile color-changing iron-containing silica gel particles with porous transparent N-isopropylacrylamide thermosensitive hydrogel on the surface. After removing the surface oil, sort out the particles with a diameter of 2.5 mm to obtain core-shell structure composite particles with color-changing / temperature dual response containing iron beads of different masses. S5-2: Soak the color-changing / temperature-responsive composite particles obtained in step S5-1 in anhydrous ethanol at room temperature for 3 days, replacing the anhydrous ethanol every 12 hours. Then soak them in sterile deionized water at room temperature for 3 days, replacing the deionized water every 12 hours. Finally, store them in sterile deionized water for later use.
3. The preparation method according to claim 2, characterized in that: In step S4, the mass ratio of the active dry yeast to N-isopropylacrylamide monomer is 1:
4.
4. The preparation method according to claim 2, characterized in that: In step S4, the glucose mass fraction in the yeast activation solution is 5%~10%.
5. The preparation method according to claim 2, characterized in that: In step S4, the mass fraction of wheat gliadin in the porous transparent N-isopropylacrylamide thermosensitive hydrogel is 12%~15%.
6. The application of the color-changing / temperature-responsive core-shell composite particles prepared by the method of claim 2 in the suspension culture of mesenchymal stem cells.
7. A method for culturing mesenchymal stem cells in suspension using the color-changing / temperature-responsive core-shell composite particles prepared by the method of claim 2, characterized in that: Mesenchymal stem cells (MSCs) were cultured adherently on nucleoshell composite particles of varying masses that exhibited both color change and temperature response. A static magnetic field was used to suspend the cell-attached composite particles in a uniform, layered manner within the culture system, maintaining them at a relative standstill. When the MSCs reached a certain density, the temperature was lowered to below 32°C. The volume phase transition properties of a porous, transparent N-isopropylacrylamide thermosensitive hydrogel were utilized to allow the adherent cells to detach automatically from the nucleoshell composite particles. After the cells detached, the direction of the static magnetic field was changed, causing the nucleoshell composite particles to aggregate and become fixed at the bottom of the culture container. The cell suspension above the nucleoshell composite particles was then aspirated and centrifuged to obtain the MSC precipitate.
8. The method according to claim 7, characterized in that: The method specifically includes the following steps: S1: Different masses of color-changing / temperature-responsive core-shell composite particles are laid at the bottom of the culture container. The mesenchymal stem cells to be inoculated are then added to an appropriate amount of complete culture medium and mixed well before being transferred into the culture container. The culture container is then placed vertically in an incubator at 37°C and 5% CO2. A static magnetic field is applied above the culture container to make the core-shell composite particles with attached cells uniformly suspended in the culture system and kept relatively still. S2: After the mesenchymal stem cells in step S1 have reached 80% cell confluence, adjust the incubator temperature to 20℃ and continue culturing until all the nuclear-shell composite particles change color from colorless to blue, indicating that the mesenchymal stem cells have completely detached from the nuclear-shell composite particles. S3: After the mesenchymal stem cells have completely detached from the core-shell composite particles in step S2, turn off the static magnetic field above the culture container. After all the core-shell composite particles have naturally settled to the bottom of the culture container, apply a static magnetic field to the bottom of the culture container to cause the core-shell composite particles to aggregate and fix to the bottom of the culture container. Take the cell suspension above the core-shell composite particles, centrifuge, discard the supernatant, and obtain the mesenchymal stem cell precipitate.
9. The method according to claim 8, characterized in that: The strength of the static magnetic field is 5 mT to 1 T.
Citation Information
Patent Citations
Thermosensitive microcarrier as well as preparation technology and application method thereof
CN103409361A
Method for preparing multifunctional multilayer micro / nanometer core-shell structure
CN104474552A